Penemuan Hukum dalam Sistem Perkembangan Peradilan di Indonesia - alga hehalatu (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Legal discovery (rechtsvinding) is a fundamental element in the modern legal system, particularly in the context of legal developments in Indonesia, which continue to move in line with social and technological dynamics. Judges not only carry out the function of implementing laws, but also act as interpreters and developers of law when written regulations are inadequate. This article comprehensively discusses the concept of legal discovery, the factors underlying it, the methods of interpretation and construction used by judges and the role of legal discovery in bridging the gap between das sollen and das sein. The discussion is also accompanied by an analysis of court decisions and supporting scientific literature. The research method used is a normative juridical approach by examining primary legal sources such as statutory regulations. Normatively, this study confirms that judges in Indonesia not only play the role of